Iraq Crude Oil Exports for January, February and March 2021 - SOMO, State Oil Marketing Organization (Journal of Petroleum Research and Studies, 2023)
Table 1. Iraq Crude Oil Exports – January 2021 Table 2. Iraq Crude Oil Exports – February 2021 Table 3. Iraq Crude Oil Exports – March 2021